Preparation of multi-atom specially entangled W-class state and splitting quantum information - Wang, YaHong; Song, HeShan (Chinese science bulletin, 2009)
We give a protocol to prepare specially entangled W-class state of multi-atom which can be used to exactly teleport an arbitrarily unknown two-level two-atom state. During the process, the quantum information is split into n parts and the original quantum information can be sent to anyone of the n recipients with the other n-1 recipients＇ collaboration. In addition, we will give a suggestion to realize this scheme via QED cavity.